Differences and Correlation Analysis of Birth Weight and Overweight/Obesity in Shanghai Twin Cohort. (1st February 2021) - Liao, Ping; Wang, Wen-Jing; Yu, Hui-Ting; Zang, Jia-Jie; Qian, Nai-Si; He, Xin; Gao, Wen-Jing; Yu, Can-Qing; Li, Li-Ming; Wu, Fan
Abstract: The objective of this study was to analyze differences in birth weight and overweight/obesity in a Shanghai twin cohort. We also wanted to study their association and explore possible risk factors for the discordance of overweight/obesity within twins. This was an internal case–control study designed for twins. The 2012 Shanghai Twin Registration System baseline survey data of a total of 3417 twin pairs were statistically analyzed using SPSS22 software. Results show that the body mass index (BMI) of the Shanghai twin population increased with age. Twins with a high birth weight had a higher BMI and a higher rate of overweight and obesity; 0- to 6-year-old twins, male twins and dizygotic (DZ) twins had higher rates of overweight/obesity than other groups. The greater the discordant birth weight rate of twins, the more obvious the difference in BMI ( p < .05). There was a significant difference in overweight/obesity between twins with a relative difference of birth weight ≥15% in DZ twins ( p < .05). DZ twins, male twins and 0- to 6-year-old twins were more likely to be discordant in overweight/obese than others. The discordant birth weight within twins was not a risk factor for discordant overweight/obesity. However, attention should be paid to childhood obesity, and appropriate interventions should be made at the appropriate time. Genetics may play an important role in the occurrence and development of overweight/obesity. In conclusion, discordant growth and development in the uterus early in life may not lead to discordant weight development in the future.